PECULIARITIES OF THE CYTOKINE PROFILE OF PATIENTS WITH TYPE 2 DIABETES MELLITUS IN COMBINATION WITH AUTOIMMUNE THYROIDITIS - N. A. Kravchun; I. V. Chernyavskaya (Klinicist)
Study objective: study of the nature of changes in the immune system of patients with type 2 diabetes mellitus (DM) in combination with autoimmune thyroiditis (AIT) and without it; comparative analysis of similar indicators of patients with type 1 DM in combination with AIT and without it.Materials and methods. 104 patients at the age of 22 to 62 y.o. (57 women and 47 men) took part in the study. They were divided into 4 groups (type 2 DM, type 2 DM and AIT, type 1 DM, type 1 DM and AIT). Groups of patients who were examined regarding the state of carbohydrate and lipid metabolism, indicators of the T-cell link of the immune system, concentration of interleukin 4 (IL-4), IL-6, interferon-gamma, and leptin level, were comparable regarding their sex, age, duration of disease.Results. Unidirectional relationship between body mass index (BMI), amount of CD4 +-, CD8+- lymphocytes, level of leptin, IL-4, IL-6 concentrations and BMI and immunoregulatory index of patients with type 2 DM both with AIT and without it was determined. Patients with type 2 DM displayed decreasing activity of the T-cell link of the immune system and increasing of the concentration of pro-inflammatory cytokines irrespectively of the availability of accompanying AIT, which evidenced primary development of autoimmune processes. At the same time, positivecorrelating relationship between the level of leptin and BMI and immunoregulatory index of patients with type 2 DM both with AIT and without it was revealed (r = 0.83; р < 0.005; r = 0.77; р < 0.01; r = 0.9; р < 0.001, and r = 0.53; р < 0.05 respectively), which demonstrates autoimmune directivity of immune system disorders in combination with metabolic shifts.Conclusion. For the purpose of performance of simultaneous correction of metabolic and immunological disorders of patients with type 2 DM, it is necessary to determine immunological indicators (of the CD+- range of lymphocytes). The latter is caused with higher occurrence of AIT with patients with type 2 DM as compared to the general population.